Selective androgen receptor modulators: a critical appraisal - Bond, Peter; Smit, Diederik L.; Verdegaal, Tijs; de Ronde, Willem (Frontiers in Endocrinology, 2025)
The concept of selective androgen receptor modulators (SARMs) was introduced in 1999 in analogy to selective estrogen receptor modulators (SERMs). The primary goal was to separate the unwanted androgenic or virilizing effects from the anabolic or myotrophic effects. This separation would result from tissue-selective effects. In this paper, we critically appraise the evidence behind SARMs’ purported tissue selectivity with emphasis on historical androgen research, which, in essence, tried to achieve the same goal by modifying the steroid nucleus. While SARMs demonstrate favorable ‘anabolic-androgenic ratios’ in preclinical studies, much of this apparent selectivity may stem from a lack of steroidal metabolism — such as 5α-reduction and 3α/β-reduction — when compared with steroidal androgens that are susceptible to these metabolic pathways. Emerging evidence suggests that differential recruitment of coregulators and differences in activation of nongenomic signaling pathways may contribute to tissue-selective effects, but it remains unclear whether this translates to clinically meaningful tissue selectivity. Clinical trials reveal some efficacy of SARMs in terms of improvements in body composition or anti-tumor activity in advanced breast cancer, yet these results might equally well have been achieved with conventional androgens as head-to-head trials are lacking. Furthermore, the absence of estrogenic activity poses a clinical challenge, especially regarding bone health and sexual function in men. Overall, while SARMs present an attractive therapeutic concept, robust evidence supporting their superiority over traditional androgens remains incomplete, warranting cautious interpretation and further comparative research.